2012
DOI: 10.3233/jad-2012-121207
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Anatomical Correlates of Gait Dysfunction in Alzheimer's Disease

Abstract: We conducted a cross-sectional study to investigate the clinical and anatomical correlates of gait dysfunction in advanced Alzheimer's disease (AD). A comprehensive clinical protocol that included cognitive, functional, behavioral, and motor variables was administered to patients with probable AD (n = 100), possible AD (n = 17), and AD with cerebrovascular disease (AD + CVD) (n = 27). Gait dysfunction was evaluated with the Rating Scale for Gait Evaluation in Cognitive Deterioration and magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The volume of their hippocampus was measured and corrected for their intracranial volume. Individual hippocampal atrophy was assessed using voxel-based morphometry, as described in (Olazaran et al, 2013). Hippocampal volume measurements were calculated using the freely available software FreeSurfer (http://surfer.nmr.mgh.harvard.edu/).…”
Section: Additional Analysismentioning
confidence: 99%
“…The volume of their hippocampus was measured and corrected for their intracranial volume. Individual hippocampal atrophy was assessed using voxel-based morphometry, as described in (Olazaran et al, 2013). Hippocampal volume measurements were calculated using the freely available software FreeSurfer (http://surfer.nmr.mgh.harvard.edu/).…”
Section: Additional Analysismentioning
confidence: 99%
“…[6][7][8][9] There is an increasing understanding that motor impairments contribute to overall AD severity, and that there is a need for ameliorating these impairments. For example, gait impairments can decrease quality of life by reducing mobility; increasing risk for injuries due to falling and increasing the likelihood of institutionalization once the ability to walk is lost 10,11 . Motor dysfunction is a reliable predictor for the development of AD, and can also predict levels of cognitive dysfunction and mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although cognitive symptoms are primary, studies have shown that walking difficulties and motor dysfunction are also common [1, 2]. These mobility impairments may have a common cause with cognitive decline [3] and may be closely associated with neurodegeneration and AD pathology AD, including gray matter degeneration, white matter damage, and amyloid-beta accumulation [4, 5]. …”
Section: Introductionmentioning
confidence: 99%